122 Functional correlates of abnormal temporal discrimination in adult onset primary torsion dystonia patients and first-degree relatives. Issue 3 (9th February 2012) - Whelan, R; Bradley, D; Kimmich, O; O'Riordan, S; Reilly, R B; Hutchinson, M
Abstract : Background: The Temporal Discrimination Threshold (TDT) is the shortest time interval at which a subject can detect that two stimuli are asynchronous. The TDT is abnormal in patients with AOPTD and approximately 50% of their unaffected relatives. Putaminal activation positively correlates with effective temporal discrimination in healthy subjects. We hypothesised that relatives of AOPTD patients with abnormal TDT thresholds would have hypoactivation of the putamen, vs relatives with normal TDT. Methods: Eleven AOPTD patients (median age =48.4 years), 12 first-degree relatives with abnormal TDT (median age =46.9 years), 12 first-degree relatives with normal TDT (median age =40.8 years), and 12 healthy controls (median age =48.9 years) underwent fMRI scanning while judging if two stimuli were synchronous or asynchronous. The significance threshold was p<0.05, family-wise error corrected across the whole-brain. Results: Relatives with abnormal TDTs had less activation than relatives with normal TDTs in the putamen (z=7.1) and in the middle frontal gyrus (z=6.83). Patients had less activation in the middle frontal gyrus (z=5.8) and in the medial frontal gyrus (z=5.45) than controls. Relatives with abnormal TDTs had less activation than patients in the middle frontal gyus (z=5.92) and the pre-SMA (z=5.90). Conclusions: Temporal processing is abnormal in unaffected first-degree relatives of sporadic AOPTD patients and is due to disordered putaminal processing.